The Influence of Product Quality, Price, and Service Quality on Customer Loyalty (A Study on Consumers of Klashica Cafe in South Tangerang) - Malau, Junior; Vildayanti, Rina Ayu (Sean Institute, 2025)
This study examines how product quality, price, and service quality shape customer loyalty in a café setting in BSD City. Grounded in relationship marketing and service quality theory, the research applies a quantitative, cross-sectional design using a structured questionnaire administered to café patrons. Reliability and validity were confirmed prior to estimating the model with multiple regression. Results show that product quality, price fairness, and service excellence each exert positive and significant influences on loyalty. Consistent taste and presentation, transparent pricing, and responsive, empathetic interactions strengthen repeat patronage and willingness to recommend. The study contributes by integrating product, price, and service drivers into a unified loyalty framework for an urban developing market. Managerially, owners should standardize product specifications, communicate clear price policies, and train frontline staff to deliver timely, courteous, and personalized service, thereby building durable loyalty and sustaining competitive advantage in a crowded café landscape, and foster positive word-of-mouth advocacy.